Glucocorticoid receptor dimerization is required for survival in septic shock via suppression of interleukin-1 in macrophages - Kleiman, Anna; Hübner, Sabine; Hofer, Stefan (The FASEB journal, 2011)
Sepsis is controlled by endogenous glucocorticoids (GCs). Previous studies provided evidence that crosstalk of the monomeric GC receptor (GR) with proinflammatory transcription factors is the crucial mechanism underlying the suppressive GC effect. Here we demonstrate that mice with a dimerization-deficient GR (GRdim) are highly susceptible to sepsis in 2 different models, namely cecal ligation and puncture and lipopolysaccharide (LPS)-induced septic shock. TNF-α is normally regulated in these mice, but down-regulation of IL-6 and IL-1β is diminished. LPS-treated macrophages derived from GRdim mice are largely resistant to GC actions in vitro in terms of morphology, surface marker expression, and gene expression. Treatment with recombinant IL-1 receptor antagonist improved survival of GRdim mice and mice lacking the GR in macrophages (GRLysMCre) mice. This suggests that regulation of IL-1β in macrophages by GCs is pivotal to control sepsis.—Kleiman, A., Hübner, S., Rodriguez Parkitna, J. M., Neumann, A., Hofer, S., Weigand, M. A., Bauer, M., Schmid, W., Schütz, G., Libert, C., Reichardt, H. M., Tuckermann, J. P. Glucocorticoid receptor dimerization is required for survival in septic shock via suppression of interleukin-1 in macrophages.
Gesehen am 06.02.2019